2019
DOI: 10.1242/dmm.036681
|View full text |Cite
|
Sign up to set email alerts
|

VPS13A, a closely associated mitochondrial protein, is required for efficient lysosomal degradation

Abstract: Members of the VPS13 family are associated with various human diseases. In particular, the loss of function of VPS13A leads to chorea-acanthocytosis (ChAc), a rare neurodegenerative disease without available curative treatments. Autophagy has been considered a promising therapeutic target because the absence of VPS13A causes a defective autophagy flux. However, the mechanistic details of this deficiency are unknown. Here, we identified Rab7A as an interactor of one of the VPS13 family members in Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 101 publications
(122 reference statements)
8
88
0
Order By: Relevance
“…In order to shed light if this is due to an overproduction of lysosomal vesicles or due a deficit in downstream fusion of these compartments, further experiments need to be conducted. Even though we did not comprehensively investigate the underlying mechanism, both possibilities suggest an impairment of this pathway, as was described previously [25,32]. The altered transport features of these compartments can be a secondary effect due to mitochondrial failure to provide enough ATP to the cells or it can be indicative that the underlying rails-the microtubules-are defective.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In order to shed light if this is due to an overproduction of lysosomal vesicles or due a deficit in downstream fusion of these compartments, further experiments need to be conducted. Even though we did not comprehensively investigate the underlying mechanism, both possibilities suggest an impairment of this pathway, as was described previously [25,32]. The altered transport features of these compartments can be a secondary effect due to mitochondrial failure to provide enough ATP to the cells or it can be indicative that the underlying rails-the microtubules-are defective.…”
Section: Discussionmentioning
confidence: 88%
“…Major advances in understanding the pathomechanism of ChAc and the function of chorein and its orthologues have been made recently [7][8][9][10]25]. Still, the main focus of the scientific community lies on the investigation of erythrocyte and medium spiny neuron (MSN) phenotypes as the primarily affected cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cutting-edge microscopy studies have detected the establishment of physical contacts between lysosomes and mitochondria in healthy cells in the absence of damage stimulus [1,233]. Besides, the latest discoveries in the field point to RAB7 as a master coordinator of these contacts [6,7,[234][235][236] (Fig 6).…”
Section: Composition and Functions Of Contacts Between Mitochondria Amentioning
confidence: 99%
“…This interaction increases upon ª 2019 The Authors EMBO reports 20: e47928 | 2019 autophagy induction by starvation and has been proposed to be key for autophagosome-lysosome fusion [234]. A recent study indicates that lysosomal RAB7 immunoprecipitates and partially colocalizes with mitochondrial VPS13A in HeLa cells and that the absence of VPS13A causes impaired lysosomal degradation [236]. Moreover, a different study has identified a hydrophobic cavity in the structure of this protein and has proved its capacity to bind and transfer phospholipids between two membranes [238].…”
Section: Composition and Functions Of Contacts Between Mitochondria Amentioning
confidence: 99%
“…Hsu et al described reversible translocation of Rab5 from early endosomes to mitochondria at MCS under conditions of oxidative stress and active membrane‐bound Rab7 was found to promote mitochondria‐lysosome MCS that mark sites of mitochondrial fission . Moreover, the role of Vps13A, which interacts with Rab7 on LE/Lys, in lysosomal degradation was recently linked to its localization at the mitochondria‐LE/Lys interface …”
Section: Regulation and Composition Of Endocytic Organelle Mcsmentioning
confidence: 99%